Lattice instability, anharmonicity and Raman spectra of BaO under high pressure: A first principles study. (November 2022) - Lavanya, K.; Yedukondalu, N.; Rakesh Roshan, S.C.; Dabhi, Shweta D.; Sripada, Suresh; Sainath, M.; Ehm, Lars; Parise, John B.
Abstract: Alkaline-earth metal oxides, MgO and CaO dominate Earth's lower mantle, therefore, exploring high-pressure behavior of these compounds is of significant geophysical research interest. Among the alkaline-earth metal oxides, BaO exhibits rich polymorphism in the pressure range of 0–1.5 Mbar. Static enthalpy calculations revealed that BaO undergoes a pressure-induced structural phase transition from NaCl-type (B1) → NiAs-type (B8) → distorted CsCl-type (d-B2) → CsCl-type (B2) at 5.1, 19.5 and 120 GPa, respectively. Transitions B1 → B8 and B8 → d-B2 are found to be first order in nature whereas d-B2 → B2 is a second order or weak first-order phase transition with displacive nature. Interestingly, the d-B2 phase shows stability over a wide pressure range of ∼19.5–113 GPa. Mechanical and dynamical stabilities of ambient and high-pressure phases are demonstrated through the computed second-order elastic constants and phonon dispersion curves, respectively. Under high pressure, significant phonon softening and soft phonon mode along the M-direction are observed for B8, d-B2 and B2 phases, respectively. Pressure-dependent Raman spectra suggest a phase transition from d-B2 to a Raman inactive phase under high pressure. Overall, the present study provides a comprehensive understanding of lattice dynamics and the underlying mechanisms behind pressure-induced structural phase transitions in BaO. Highlights: Pressure induced structural phase transitions. Understanding structural transition mechanisms. Elastic constants and mechanical properties under high pressure. Phonon softening, lattice instabilities and anharmonicity. Raman spectra under high pressure.